The concept of intrinsic versus extrinsic apoptosis - Lossi, Laura (Biochemical journal, 2022)
Regulated cell death is a vital and dynamic process in multicellular organisms that maintains tissue homeostasis and eliminates potentially dangerous cells. Apoptosis, one of the better-known forms of regulated cell death, is activated when cell-surface death receptors like Fas are engaged by their ligands (the extrinsic pathway) or when BCL-2-family pro-apoptotic proteins cause the permeabilization of the mitochondrial outer membrane (the intrinsic pathway). Both the intrinsic and extrinsic pathways of apoptosis lead to the activation of a family of proteases, the caspases, which are responsible for the final cell demise in the so-called execution phase of apoptosis. In this review, I will first discuss the most common types of regulated cell death on a morphological basis. I will then consider in detail the molecular pathways of intrinsic and extrinsic apoptosis, discussing how they are activated in response to specific stimuli and are sometimes overlapping. In-depth knowledge of the cellular mechanisms of apoptosis is becoming more and more important not only in the field of cellular and molecular biology but also for its translational potential in several pathologies, including neurodegeneration and cancer.